Protecting olympic participants from COVID-19: the trialled and tested process - Pigozzi, F.; Wolfarth, B.; Rodriguez, A. C.; Steinacker, J. M.; Badtieva, V.; Bilzon, J. L. J.; Schneider, C.; Roberts, W. O.; Swart, J.; Constantinou, D.; Dohi, M.; Papadopoulou, T.; et al. (British Journal of Sports Medicine, 2021)
The COVID-19 pandemic has created many challenges to ensure a safe environment for competitive sport. While modern medicine has already developed effective protocols for the treatment and prevention of the disease, there are serious concerns about hosting a sporting event of the scale of the Olympic Games, where more than 11 000 athletes from over 200 nations are expected to participate. Accordingly, there have been many calls to cancel the Tokyo Olympic Games, also known as Tokyo 2020, in both the international press and the scientific literature. A recent perspective published in the New England Journal of Medicine (NEJM)1 highlights the complexity and risks of convening the Tokyo Olympic Games during the COVID-19 pandemic. Despite the many uncertainties, much has been learnt over the past 18 months and many policies trialled and tested to protect athletes during sports participation.